Perceptions and Attitudes Towards Late Marriage and Premarital Fertility in Rural South Africa - (:unkn) unknown (My University, 2004)
Premarital fertility is defined as fertility before first marriage. In South Africa, in 1998, according to the Demographic and Health Survey (DHS), about 65% of women under 25 had had a premarital birth and close to 39% of all births were premarital. Although total fertility rate had decreased drastically (down to 2.9), trends showed that premarital fertility was increasing. We investigated perceptions and attitudes towards late marriage and premarital fertility to understand this phenomenon better, and to inform programmes pertaining to family welfare, reproductive health and HIV/AIDS. In order to understand the increase in premarital fertility in South Africa, the qualitative study focused on the perceptions and attitudes in the Shangaan culture in Agincourt, in rural Bushbuckridge. In this society, sexuality, pregnancy and marriage were linked traditionally. Nowadays, parental social control over adolescents has relaxed but premarital births remain stigmatised. Although adolescent fertility has always existed, only recently has it become a social problem because most young mothers are unmarried. The perceptions and attitudes towards premarital fertility reveal social mutations in parental control over adolescent sexuality as well as in moral standards. A majority of persons interviewed expressed negative perceptions towards a birth before first marriage. The reasons varied and included: school drop out for the mother, economic hardship, parental stigmatisation, health risk for the mother because of unprotected sex (STD/HIV), and for the child because of malnutrition (kwashiorkor).
Keywords: African Research